Comparison of Manual and Mechanized Tree Felling Operations in Strip Plantations of Haryana State - Ramesh Singh, D. H. (Indian Forester, 2000)
Tree harvesting in strip forests is done by the Forest Department of Haryana State. Routine harvesting was done through employing daily wage paid labourers mostly restricted during winter months as the la.bourers were migratory. Recently the skills have been acquired by resident labourers and efforts are being made by them to mechanize felling operations. Work study was made in the Sirsa Range of Fatehabad Division where one such mechanized outfit was felling trees along side another group doing entirely manual operations. The study which has been moderated by sharing of experience has indicated that mechanization has greater efficiency upto a measured level of 26.5% in felling and also leads to capital formation. It is suggested that the maintenance and care of machines is done better by private sector and hence they should be encouraged to do so and the Forest Department should take advantage of speed of felling. Also the mechanization would be of greater relevance in block forests in plains where movement of trolley mounted genset is less.